2019
DOI: 10.1111/cge.13605
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous CTNNB1 and TBX4 variants in a patient with abnormal lung growth, pulmonary hypertension, microcephaly, and spasticity

Abstract: The canonical wingless (Wnt) and fibroblast growth factor (FGF) signaling pathways involving CTNNB1 and TBX4, respectively, are crucial for the regulation of human development. Perturbations of these pathways and disruptions from biological homeostasis have been associated with abnormal morphogenesis of multiple organs, including the lung. The aim of this study was to identify the underlying genetic cause of abnormal lung growth, pulmonary hypertension (PAH), severe microcephaly, and muscle spasticity in a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…2 TBX4 mutations are thought to cause developmental lung abnormalities due to its role in mesoderm induction and specification during fetal lung development. 2,8 Given these structural manifestations, the role of glucocorticoids in these patients is unclear, even in the setting of concurrent PIG. As glucocorticoids promote lung maturity and decrease parenchymal and airway inflammation, they may play a role in improving respiratory status in children with various etiologies of lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…2 TBX4 mutations are thought to cause developmental lung abnormalities due to its role in mesoderm induction and specification during fetal lung development. 2,8 Given these structural manifestations, the role of glucocorticoids in these patients is unclear, even in the setting of concurrent PIG. As glucocorticoids promote lung maturity and decrease parenchymal and airway inflammation, they may play a role in improving respiratory status in children with various etiologies of lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies revealed that modulation of the Wnt pathway by gene knockouts resulted in early lethality often associated with impaired respiratory development due to prevention of distal lung buds formation [ 37 ]. Recently, we also reported variants in CTNNB1 and TBX4 , encoding crucial members of the Wnt and FGF signaling, in a newborn with abnormal lung growth, PAH, severe microcephaly, and spasticity, suggesting that mutations in these genes could act synergistically resulting in a lethal respiratory failure during the neonatal period [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note the short fourth and fifth rays in the feet of both parents in Family 1 and the mother in Family 2, and the wide gap between the first and second toes in both parents of Family 2. hypoplasia, and alveolar growth abnormality. [14][15][16][17]41 Of note, the F1-IV:5 fetus also showed atresia of external auditory canal. We are not aware of previous reports of abnormalities in external ear development in association with TBX4 variants or CNVs in humans or other organisms, but there are reports of deletions and/or duplications of the region containing the TBX4 gene associated with hearing loss and abnormal auricles.…”
mentioning
confidence: 90%
“…13 Recently, the occurrence of rare coding TBX4 variants with putative hypomorphic non-coding mutations in one of its lung enhancers has been recognized as a cause of pediatric pulmonary hypertension and lethal lung developmental disease, which is associated with congenital heart disease, foot anomalies, and developmental disability. [14][15][16][17] T-box genes are a family of evolutionary-conserved transcription factors characterized by a shared DNA-binding domain. They have restricted spatio-temporal patterns of expression during embryogenesis, and play distinct roles during organogenesis as documented by genetic studies performed in animal models and humans.…”
mentioning
confidence: 99%